A knowledge framework and decision tool for fdis using multi-Criteria analysis - Napaporn Reeveerakul (2018)
To address the issues associated with FDIs' potential relocation, divestment or transfer of plant, the research aims to provide a knowledgedecision on FDIs and present a framework that supports manufacturers to consider on their performance in Northern Region Industrial Estate (NRIE), Thailand to become sustainable. An integrated framework is proposed based on two main aspects of finance and supply chain and infrastructure in dynamic analysis. Analysis on financial situation, the Net Present Value (NPV), is applied to estimate future cash flow of FDIs' investment. Further, to support a decision-maker using supply chain simulation tool is of most applicable circumstance. The simulation tool is applied to a case study of Make-to-Order environment. The supply chain system is constructed based on Supply Chain Operations References (SCOR) model. ARENA simulation is used to describe supply chain processes by interrelating to a web application which is a friendly tool for decision-makers. © 2013 Inderscience Enterprises Ltd.